Splitting solver with immersed boundary extension for the analysis of backward-facing step flow - Zamani, Ngali; Kahar, Osman; Nasrul Hadi, Johari (AIP Publishing LLC., 2012)
Flow analysis of backward-facing step is claimed to be a necessity when it comes to Computational Fluid Dynamics solver validation. The turbulence development with both separation and reattachment passing through the step has become the practical challenge for solver developers ever since the numerical computation revolution started. In-line with the trend, this work is predestined to further validate the use of Splitting velocity-pressure coupling method with immersed boundary extension for unsteady Navier-Stokes flow solver. The comparison is launched with steady numerical results via established software for commonly used benchmark backward-facing step construction. Flow parameters in both solvers are set equivalent to Reynolds number of 1000. The assessment is carried out when the flow has reached steady flow condition. The streamwise velocity profiles are well-matched where the maximum error is within 4%. The reattachment distance measured from the developed solver is also in good agreement with the reference results with only 1.84% difference recorded. The comparison proves that the solver developed in this work could become a very handy alternative especially when we look at the solver simplicity and the number of nodes it consumes to obtain comparable results.